Empowerment of the PKK Group in Tanjungan Village, Mojokerto Regency through Innovation of Globe Amaranth (Gomphrena globosa) Herbal Tea - Kartini, Kartini; Setyaningrum, Idfi; Hidayat, Ramdan; Pudjibudojo, Jatie K. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Community empowerment is a strategic effort to enhance the capacity and self-reliance of local groups, particularly women, in supporting development based on regional potential. This program aimed to empower the PKK group in Tanjungan Village, Mojokerto Regency, through the development of an innovative herbal tea product made from globe amaranth flowers (Gomphrena globosa), which are known for their functional health benefits. The activities included assistance in the cultivation, harvesting, and post-harvest handling of globe amaranth flowers; training in herbal tea processing; and support in production and packaging aspects. The results showed that the PKK group members were able to process the flowers into a consumable herbal tea product with appealing presentation and promising market potential. Moreover, the training significantly improved participants’ knowledge regarding the health benefits of globe amaranth and herbal product processing techniques. Pre- and post-training evaluations revealed a 36% increase in participants' knowledge. This initiative also fostered entrepreneurial skills in herbal-based products, offering an alternative source of income for the community. It is expected that this innovation will not only improve local welfare but also support the sustainable development of local potential.